The implementation of ict in the design of didactic strategies for the development of socio-emotional skills in the post-pandemic - Parra Gaitan, Lina Maria; Bernal Vargas, Liliana; Neira-Piñeros, Maria (Rastros Rostros, 2023)
When social activities were shut down due to covid-19 middle childhood changed the way they used to feel, think, and interact with others, showing feelings of fear, uncertainty, insecurity, depression and anxiety. This happened because at this stage of development, children are more interested in their environment being more susceptible to life changes, indicating that socio-emotional education is essential to counteract these effects. Therefore, the purpose of this research is to strengthen Colombian middle childhood socio-emotional skills after the pandemic on a virtual learning environment, carrying on three studies: the first study sought to identify the level of affectation during social isolation in the Colombian middle childhood by covid-19 through a narrative review, the second study had the objective of recognizing the methodological characteristics in order to design an effective didactic strategy to develop socioemotional skills, using a systematic review, and the third study and last purpose is Design and evaluate the didactic strategy with the opinion of experts. Additionally, it was found that ict the increase in physical and psychological violence during lock down had a great impact on children, affecting the emotional aspect, the socialization processes, learning and low self-esteem. and it is concluded that contribute to the enrichment of didactic strategies that allow the development of active learning, where socio-emotional education fits perfectly.